Leveling up learning effectiveness in STEM education through gamification: an empirical study on behavioral intention and digital literacy among undergraduate students in Kuwait - Aljamaan, Abrar; Alsaber, Ahmad; Emmanuel, Coffie; Alkandari, Anwaar (Frontiers in Education, 2025)
IntroductionThis study seeks to investigate the influence of gamification on learning effectiveness in STEM education among undergraduate students in Kuwait. Specifically, the present research explores how various constructs —performance expectation, effort expectation, social influence, and digital literacy—impact students' behavioral intention and willingness to adopt gamification as an integrated part of their learning process in mathematics courses. A series of hypotheses are developed to explore direct and indirect relationships between variables.MethodsA cross-sectional quantitative study is conducted using a structured questionnaire administered to undergraduate students enrolled in mathematics courses at private universities in Kuwait. The questionnaire is designed based on an extension of the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, to further measure the impacts of learning motivation, learning enjoyment, and digital literacy. Data are analyzed using partial least squares structural equation modeling (PLS-SEM) to validate the relationships between the constructs and evaluate the overall model fit.ResultsFindings reveal that two key factors—performance expectancy (β = 0.674, p < 0.001) and learning motivation (β = 0.562, p < 0.001)—have substantial direct impacts on students' behavioral intention to use gamification in their learning. Moreover, effort expectancy is shown to have a positive influence on learning enjoyment (β = 0.399, p < 0.001), while social influence also plays a significant role in enhancing learning enjoyment (β = 0.099, p = 0.029). Interestingly, in this study, we also find that behavioral intention is a strong predictor of the intention to adopt gamification in learning (β = 0.789, p < 0.001). Results also highlight indirect effects, with learning motivation bridging performance expectancy and behavioral intention.DiscussionPerformance expectancy and learning motivation are two primary indicators for students' behavioral intentions to adopt gamification in STEM education. Thus, by utilizing gamified learning tools to boost motivation and enjoyment, educators can significantly improve student engagement and their willingness to use gamification as a learning tool. In order to most effectively leverage the potential for gamification, it is necessary for educators to focus on strategies that not only enhance the perceived benefits of gamification, but also increase students' intrinsic motivation.